2014
DOI: 10.1371/journal.pone.0096878
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Molecular Profiling and Chemical Imaging to Elucidate Fibroblast-Microenvironment Impact on Cancer Cell Phenotype and Endocrine Resistance in Breast Cancer

Abstract: The tumor microenvironment is known to play a key role in altering the properties and behavior of nearby cancer cells. Its influence on resistance to endocrine therapy and cancer relapse, however, is poorly understood. Here we investigate the interaction of mammary fibroblasts and estrogen receptor-positive breast cancer cells in three-dimensional culture models in order to characterize gene expression, cellular changes, and the secreted protein factors involved in the cellular cross-talk. We show that fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
(75 reference statements)
0
28
0
Order By: Relevance
“…2e) 258 . Analysis of conditioned media from co-cultured cancer cells showed a >5-fold upregulation of 46 proteins (including MMPs and TGFβ) compared with media from non co-cultured breast cancer cells 258 .…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…2e) 258 . Analysis of conditioned media from co-cultured cancer cells showed a >5-fold upregulation of 46 proteins (including MMPs and TGFβ) compared with media from non co-cultured breast cancer cells 258 .…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%
“…2e) 258 . Analysis of conditioned media from co-cultured cancer cells showed a >5-fold upregulation of 46 proteins (including MMPs and TGFβ) compared with media from non co-cultured breast cancer cells 258 . Other studies have shown that the loss of caveolin 1 expression in breast cancer stromal tissue enables prediction of a lack of response to tamoxifen, an ER antagonist 259,260 .…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%
“…These relationships arise from the fact that stromal or abnormal fibrotic regions are often the surrounding environment in which pathologic processes of the epithelium take place. For example, FT-IR investigations of co-culture of fibroblasts with breast cancer cell lines highlight the interaction between the former and the latter (Holton, S. et al, 2011; Holton et al, 2014; Holton, S.E. et al, 2011).…”
Section: Fibrosis As the Target Regionmentioning
confidence: 99%
“…In particular they found that fibronectin, lysyl oxidase, SPARC and TIMP3 expression levels were associated to the prognosis of patients with breast cancer whereas levels of tenascin C were associated to resistance to treatment with tamoxifen. A recent paper by Holton et al [38] using 3D cultures and Fourier transform infrared spectroscopic imaging shows that fibroblasts induce epithelial to mesenchymal transition in cancer cells together with a downregulation in ERα levels. Our work also suggests that stromal factors modulate response to endocrine resistance.…”
Section: The Extracellular Matrix Cancer Associated Fibroblasts and mentioning
confidence: 99%